Eind the roots of equation x²-3x-m(m+3)=0
Where m is constant.
Answers
Answered by
1
Step-by-step explanation:
10th
Maths
Quadratic Equations
Solutions of Quadratic Equations
The roots of the equation x...
MATHS
The roots of the equation x
2
−3x−m(m+3)=0, where m is a constant, are
EASY
Share
Study later
ANSWER
Given: equation x
2
−3x−m(m+3)=0, where m is a constant
To find the roots of the equation
Sol: the given equation is of form ax
2
+bx+c=0∴a=1,b=−3,c=−m(m+3)
We know the roots of the equation can be find out using the formula,
x=
2a
−b±
b
2
−4ac
Substituting the values of a, b, c, we get
x=
2
−(−3)±
(−3)
2
−4(1)(−m(m+3)
⟹x=
2
3±
9+4m
2
+12m
⟹x=
2
3±(2m+3)
or x=
2
3+(2m+3)
,x=
2
3−(2m+3)
⟹x=m+3,x=−m are the required roots of the equation.
Similar questions